2016
DOI: 10.1142/s0219519416500871
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Solid–liquid Suspension and Scale-Up of Agarose Gel Activation Reactor

Abstract: Agarose gel activation reaction, which is of great importance in preparing the carrier of the column packing material for blood purification, would be significantly influenced by the configuration and parameter of reactor. In order to optimize the structure design of the reactor and operating parameters of the process, the characteristics of suspension system composed of agarose gel, NaOH, water, 3-allyl bromide, and activated alumina were simulated numerically utilizing an Eulerian multiphase flow model and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The appropriate scale-up index x under this condition was 0.93, closer to the scale-up criterion with the same blade tip speed (x = 1) rather than constant unit volume power (x = 2/3). Zhou et al [12] found that the velocity field was similar before and after scaling up according to the same blade tip speed. The solid concentration distribution in most regions of the tank was relatively uniform, with a high local solid volume fraction only appearing at the bottom of the stirring tank and near the baffle.…”
Section: Introductionmentioning
confidence: 95%
“…The appropriate scale-up index x under this condition was 0.93, closer to the scale-up criterion with the same blade tip speed (x = 1) rather than constant unit volume power (x = 2/3). Zhou et al [12] found that the velocity field was similar before and after scaling up according to the same blade tip speed. The solid concentration distribution in most regions of the tank was relatively uniform, with a high local solid volume fraction only appearing at the bottom of the stirring tank and near the baffle.…”
Section: Introductionmentioning
confidence: 95%